Gestión directiva y su incidencia en el trabajo en equipo de la unidad educativa José Rodríguez la bandera, año 2021. manual de estrategias de habilidades blandas y duras. - Huacón García, Cecilia Margoth (2021)
The Educational Unit "José Rodríguez Labandera", located in the Quevedo canton, will carry out a study on Directive Management, with the participation of the work team, as this will benefit the institution. This research work is aimed at solving the main problem identified in the aforementioned educational organization, dedicated to the comprehensive training of students in the canton. Its objective is to evaluate the incidence of Directive Management in the teamwork of the José Rodríguez Labandera Educational Unit, year 2021; and the specific ones to determine the incidence of the Directive Management in the fulfillment of the activities of the Educational Unit José Rodríguez Labandera; investigate the development of teamwork in the execution of activities in the José Rodríguez Labandera Educational Unit; Identify the effect of Directive Management on the development of teamwork at the José Rodríguez Labandera Educational Unit. To achieve these objectives, an applied, descriptive and bibliographic research was carried out that allowed to analyze and interpret the results achieved, likewise, inductive, deductive and analytical methodology was used, which allowed a reflective and critical analysis in order to arrive at reality; In addition, using research techniques such as interviews, observation, surveys and questionnaires with structured questions, the same ones that were applied according to the established sample so that later the relevant tabulation and analysis of the results is carried out; from where it is possible to determine the causes of the directive management and its incidence in the teamwork of the educational unit. The research will contribute to establish the current situation of Directive Management and the application of soft and hard skills as the main characteristic of the pedagogical development of the “José Rodríguez Labandera” Educational Unit. The result of this information will be used to identify the strengths and weaknesses of soft and hard skills in directive management in work teams. This study will allow, apart from knowing the current situation to be investigated of the Educational Unit to project itself towards a pedagogical and professional future seeking to achieve the proposed objectives for a solution that favors everyone. Keywords: Management-Directive management-Teamwork-Soft and hard skills-Educational Unit